Structure and meiotic behaviour of B chromosomes in Sphaerium corneum/S. nucleus complex (Bivalvia: Sphaeriidae) - Kořínková, Tereza; Král, Jiří (Genetica, 2011)
Karyotypes of eight populations of Sphaerium corneum and two populations of S. nucleus (Bivalvia: Sphaeriidae) from central Europe were compared. The basic set of these hermaphroditic molluscs is formed by 30 biarmed autosomes and exhibits only slight interpopulational variation in morphology. These differences are not species-specific. One pair of nucleolar organiser regions was detected by silver staining. The prophase and metaphase of the first meiotic division is highly modified in both species. Pachytene is followed by a diffuse stage, characterized by decondensation of chromosomes and by enhanced metabolic activity. The diffuse stage has not been reported in bivalves so far. Bivalents of the following stages are achiasmatic both in the testicular and ovarian part of the gonad. The two species are further peculiar for occurrence of B chromosomes, which is a rare phenomenon in organisms with achiasmatic meiotic systems. The small metacentric B chromosomes exhibit intra- and interindividual variability in number, they show irregular meiotic pairing and segregation (formation of bivalents or univalents), and possess larger proportional amount of constitutive heterochromatin than the A chromosomes. Interestingly, the B chromosomes also undergo decondensation during the diffuse stage like A chromosomes which may indicate their transcriptional activity.
Keywords: Male; chromozomy; Cell Nucleus; karyotypizace; profáze meiózy I; mlži; Silver Staining; heterochromatin; Karyotyping; Bivalvia; Nucleolus Organizer Region; Meiosis; mužské pohlaví; buněčné jádro; Testis; Meiotic Prophase I; barvení stříbrem; meióza; Animals; Chromosomes; ženské pohlaví; Heterochromatin; organizátor jadérka; zvířata; Ovary; testis; Female; ovarium